Promotional Tool of Marketing: An Islamic Perspective - Anwar, Muhammad; Saeed, Mohammad (Intellectual Discourse, 2013)
Promotional tools of marketing, (e.g., personal selling, advertising, sales promotion, public relations, promotional games as well as contests), play a key role in creating consumer awareness about the qualities of various products and services available on the market, and can go a long way in contributing to economic progress and social development. Muslim marketers have to be conscious of their position and role in managing marketing activities. The Qur’anic view about man and his resources should be the basis for designing promotional tools and media strategies. The latter are meant to inculcate Islamic values, build the characters of customers and marketers and uphold truth in the society. Ethical behavior in advertising and other promotional activities must be based on a strong foundation of Islamic tenets and injunctions. There is a need to develop not only general guidelines for achieving marketing goals and corporate objectives in a morally acceptable manner, but also to devise an Islamic code of marketing by Muslim marketers, corporate leaders, and sharīʿah experts.